Effects of easy soluble carbohydrate and bacterial inoculant supplementations on silage quality of frosted maize - Yusuf Konca; Selma Buyukkilic Beyzi; Maria Asuncion Gallardo Paffetti; Ismail Ulger; Mohammad Mahmodul Hasan Sohel (Acta Scientiarum. Animal Sciences, 2018)
The present experiments were conducted to assess the effects of barley, Lactobacillus bacteria and lactic acid bacteria (LAB) and enzyme mixture supplementations on chemical composition and some quality parameters of naturally frosted maize silage. The treatments were as follows; T1: Control (no supplementation, C); T2: barley 20 g kg-1, B20; T3: barley 40 g kg-1, B40; T4: 1.5 g ton-1, a mixture of LAB; and T5: 2 g ton1, a mixture LAB+enzyme, LEN. Barley supplementation to frosted maize increased dry matter (DM) (p < 0.01). The pH value was higher in LAB group (p < 0.01). Treatments supplemented LAB and LEN significantly reduced crude protein contents (p < 0.001). Lactic acid contents decreased in all treatments as compared to control group and ranged between 2.46 and 5.40% DM (p < 0.05). The metabolisable energy content was significantly higher in B40 than in B20, LAB and LEN groups. Mean Fleig points showed with an “excellent” quality silage. In conclusion, supplementation of barley, LEN and inoculation of LAB to frosted maize had a good quality silage. The LEN supplementation may be used for efficient ensiling of frosted maize due to their ability to keep its quality in low DM crop maize silage.